Development of Secondary Acute Myeloid Leukemia in a Pediatric Patient Concurrently Receiving Primary Therapy for Ewing Sarcoma. Issue 7 (October 2017) - McNew, Brandon R.; Darbro, Benjamin W.; Ma, Deqin; Gordon, David J.
Abstract : Ewing sarcoma is a pediatric bone and soft tissue sarcoma that requires intensive therapy, which can cause secondary malignancies. We present a rare case of early, treatment-related AML in a pediatric patient concurrently receiving primary therapy for Ewing sarcoma. Despite AML-directed therapy, our patient died secondary to complications of hyperleukocytosis. Cytogenetic and mutation profiling of the leukemia cells revealed the DNA-topoisomerase-II-inhibitor-associated t(9;11)(p22;q23) translocation and clonal KRAS and BRAF mutations. This report highlights the importance of monitoring for treatment-related effects in cancer therapy, as well as the need for novel, less toxic approaches in Ewing sarcoma therapy.